PENGARUH CAREER ADAPTABILITY DAN PARENTAL CAREER-RELATED BEHAVIOR TERHADAP CAREER DECISION-MAKING SELF-EFFICACY PADA SISWA SEKOLAH MENENGAH KEJURUAN - Dewi Ayu; Najma Hilman (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to examine the effect of career adaptability and parental career-related behavior on career decision-making self-efficacy (CDMSE) in Vocational High School (SMK) students. CDMSE is an important psychological factor that determines students' readiness to face career transitions. This study used a quantitative approach with an associative design. Data were obtained from 298 eleventh-grade students in three vocational high schools in Gajahmungkur District through cluster sampling techniques, using an adapted Likert scale instrument, and analyzed using multiple linear regression. The results showed that career adaptability had a positive and significant effect on CDMSE (B = 0.285; t = 6.704; p < 0.001), while parental career-related behavior had a negative and significant effect on CDMSE (B = −0.118; t = −2.558; p = 0.011). Simultaneously, both variables significantly influenced CDMSE (F = 23.026; p < 0.001) with a contribution of 13.5%. These findings emphasize the importance of strengthening career adaptability through career guidance services in schools and developing parental education programs that encourage supportive involvement and respect student autonomy in the career decision-making process.